5-Aminolevulinic Acid-Mediated Metronomic Photodynamic Therapy for Mouse Mammary Tumors - Osaki, Tomohiro; Shiomi, Hikaru; Nishimura, Takahiro; Sakanoue, Kei; Eguchi, Kazuhiro; Miyazono, Yutaka; Yamaguchi, Ryoichi; Fujita, Katsuhiko; Kuwata, Kenji; Kobayashi, Naoki; Goya, Tsuyoshi; Morii, Katsuyuki; et al. (YONAGO ACTA MEDICA, 2025)
[ABSTRACT] [Background] Metronomic photodynamic therapy (mPDT) is a novel cancer treatment strategy that uses low-dose light delivery and photosensitizers. 5-aminolevulinic acid (5-ALA), a precursor of protoporphyrin IX (PpIX) was previously used to treat human colorectal and esophageal cancer cells. However, no study has evaluated the efficacy of 5-ALA-mPDT using light of different wavelengths. Therefore, we evaluated cytotoxicity induced by 5-ALA-PDT and the antitumor effect of 5-ALA-mPDT. [Methods] In an in vitro experiment, we evaluated the cytotoxicity induced by 5-ALA-PDT using several fluence rates of light-emitting diode (LED) at wavelengths of 532 and 620 nm. In an in vivo experiment, we evaluated the antitumor effect of 5-ALA-mPDT using a newly developed implantable device emitting 532 or 620 nm. Moreover, we used in silico simulations to compare the differences in the distribution of the accumulated singlet oxygen concentrations between 532 and 620 nm. [Results] In the in vitro experiment, the percentages of late apoptotic/Dead and Dead cells in the 542-nm groups irradiated at light intensities of 1 mW/cm2 were significantly higher than those of cells in the 620-nm group. In contrast, in the in vivo experiment, the antitumor effect of mPDT using an implantable organic light-emitting diode (OLED) at 620 nm was significantly higher than that of mPDT using OLED at 542 nm. [Conclusion] Considering the results of our in silico study, the antitumor effect of 5-ALA-mPDT may be dependent on the distribution range of the accumulated singlet oxygen concentration rather than the accumulated singlet oxygen concentration.